Tax Composition and Growth : A Broad Cross-Country Perspective. (Washington, D.C. : International Monetary Fund, 2012)
We investigate the relation between changes in tax composition and long-run economic growth using a new dataset covering a broad cross-section of countries with different income levels. We specifically consider 69 countries with at least 20 years of observations on total tax revenue during the period 1970-2009-21 high-income, 23 middle-income and 25 low-income countries. To our knowledge this is the most comprehensive and up-to-date dataset on tax composition and growth. We find that increasing income taxes while reducing consumption and property taxes is associated with slower growth over the long run. We also find that: (1) among income taxes, social security contributions and personal income taxes have a stronger negative association with growth than corporate income taxes; (2) a shift from income taxes to property taxes has a strong positive association with growth; and (3) a reduction in income taxes while increasing value added and sales taxes is also associated with faster growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet